THE CULTURE OF RELIGIOUS AND EDUCATION ACTS BY FOREIGN ORIGIN MOSLEM TRAVELERS AND TRADERS IN INDONESIA - Arif Adi Wibawa (IBDA` : Jurnal Kajian Islam dan Budaya, 2016)
Culture has been and always considered as soulful and interesting topic for its concern toward ideas, opinion and human being acts since classic ages until modern time. When traveling and trading have been used also as common activity since classic period of world and Islam history, the activities and achievements surely can be recorded and be analyzed and after that can be included and classified as human culture. Arabians and Chinese who known and famous for their traveling, world expedition and trading have arrived to Indonesian archipelagoes in many centuries ago. They stayed and finally have decided this place as the last land. Communities and civilizations have been built by them. This essay recorded the coming history of them, showed their Islamic and education acts and analyzed those in the big frame of culture term, and aimed to link them as culture construction process and emphasized a statement that Islamic religious and education acts can take the parts in.